Morphological complexity promotes origination and extinction rates in ammonoids - Miao, Luyi; Liu, Xiaokang; Brayard, Arnaud; Korn, Dieter; Dai, Xu; Song, Haijun (Current biology, 2024)
The causes of heterogeneity in evolutionary rates are a key question in macroevolution. Origination and extinction rates are closely related to abiotic factors, such as climate and geography, as well as biotic factors such as taxonomic richness and morphology, which are influenced by phylogeny. Studies on the relationship between morphology and macroevolution have focused on morphological traits, including body size, shape, color, and complexity, and have proposed biological laws, such as the zero-force evolutionary law and Cope's rule. However, the relationship between morphological complexity and turnover rates remains poorly defined because of the lack of suitable measures for various subjects. Here, we establish a quantitative method, the two-dimensional ornamentation index (2D-OI), which allows the description of the ornamental complexity of ammonoids. Ammonoids are one of the most abundant and well-studied fossil groups, with complex conch structures. Ammonoids display some similarities with trilobites and mammals in terms of their high evolutionary rates; however, the underlying mechanisms remain elusive. Moreover, ammonoids exhibit marked heterogeneity in turnover rates across spatiotemporal scales and clades, making them key clades for investigating the relationship between turnover rates and morphological complexity. The results show that morphologically complex genera and species often have higher origination and extinction rates than morphologically simple taxa. Diversity fluctuations of taxa with complex ornamentation generally overimprint and control the overall net diversification rates of ammonoids. This double-edged sword of rapid evolution and increased extinction risk driven by complex morphologies has significant implications for our understanding of how species survive over geological timescales.